Embedding Patient Priorities Care in an Age-Friendly Health System. (16th December 2020) - Naik, Aanand; Kiefer, Lea; Catic, Angela; Dindo, Lillian
Abstract: Background: Patient Priorities Care (PPC) is an innovative approach to improving care for older adults with multiple morbidities. We developed a PPC training program for healthcare professionals and describe preliminary results. Methods: We implemented PPC in a geriatrics clinic. 20 staff and trainees participated on 1) how to identify patient priorities, 2) documentation in the electronic health record (EHR), and 3) strategies to align care with priorities; and received case-based audit and feedback. Results: 250 patients participated in PPC encounters. The EHR template was subsequently integrated within an Age Friendly Health System (AFHS) note. Clinicians have integrated this AFHS template for all encounters. Conclusion: PPC is a feasible approach to the care of older adults with multiple morbidities following a structured clinician training program. PPC can be effectively incorporated into the "Matter Most" component of AFHS.